Huruf Muqaṭṭa’ah: Penafsiran Ulama Kalam dan Ulama Sufi dalam Perspektif Semiotika Pierce - Qodriatinnisa, Raden Rifa; Wildan Taufiq; Dadan Rusmana (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2024)
Interpretation as a human product is greatly influenced by the science and orientation of the interpreter. This leads to different interpretations of the Qur'an. A calamite interprets the Qur'an according to his level of knowledge as a mutakallim, as well as a Sufi. This article will show a comparison of the interpretation of the letter muqattha’ah between Imam Al-Maturidi in the book of Tafsir Ta’wilat Ahli As-Sunnah who is the figure of a calam scholar and Ibn Ajibah’s interpretation in his book Al-Bahru al-Madid fi Tafsir Al-Qur’an Al-Mayid as a Sufi scholar. The method applied in this research is qualitative using library studies, research based on library data. Then the data was analyzed using Peirce's semiotic triad theory. This article will describe how the interpretation of Imam Al-Maturidi as a fictional scholar and Ibn Ajibah as a Sufi scholar against the letter muqattha’ah that is located on the opening of the letter. It will begin with the introduction of the basic theory of semiotics Peirce, the understanding of the letters muqatta’ah, as well as the interpretations of letters muqa’ah by Imam al-Muridi and Ibnu Ajibha. Then this interpretation will be applied to the triadic theory Peirces, in the form of representations, objects and interpretations. It can be concluded that a mufasir is very influential as an interpreter of signs or symbols found in the Qur'an. As in the interpretation of Al-Maturidi and Ibnu Ajibah, the Maturidi who is a mutakallim is more inclined to the submission of the meaning to Allah.